Pengaruh Gadget Terhadap Akhlak Seorang Anak - Ayu Lestari; Dea Putri; Rizky Anugrah Pardosi; Gusmaneli Gusmaneli (Pusat Riset dan Inovasi Nasional, 2023)
With the development of times and technology, humans have created tools that make it easier for humans to communicate with each other, including gadgets. Gadgets are one of the technologies that humans really need to communicate with other people. All technology has negative and positive impacts, in this case the role of parents greatly determines the impact that gadget technology has on a child's personality or morals. Children's dependence on playing gadgets cannot be separated from the role of both parents. In this modern era, parents should be smarter in introducing technology to their children. This study aims to analyze the influence that gadgets have on children's personality or morals and how parents deal with this rapidly increasing technology. The research method used is observation, documentation and interviews. Theoretically, this research is expected to add to the repertoire of social science and technology, especially sociology in the family.